Development of the Obesity Nutraceutical from Raja and Kepok Banana Peels - Kezia Elian Devina; Dono Indarto; Tri Nugraha Susilawati (Global Health Science Group, 2023)
Patients with obesity often fail to control their body weight through diet and physical activity, while the existing anti-obesity drugs have some side effects for long-term use. Banana is Indonesia's tropical fruits with the highest production, and the banana peel has become soil waste. This study aimed to analyze nutrients and active compounds of methanol extracts of raja and kepok banana peels (ERP and EKP respectively). Macro and micro-nutrient compositions of the ERP and EKP were determined using the proximate analysis, while Thin Layer Chromatography (TLC) was used to detect the ERP and EKP active compounds. The ERP contained 0.11% crude fibers, 4.44% fat, and 58.08% carbohydrates, different from the EKP (4.25% protein, 20.95% water, and 14.45% minerals). By contrast, both the ERP and EKP contained flavonoids, phenols, tannins, alkaloids, and saponins. In conclusion, ERP is potentially developed as a nutraceutical for obesity treatment in the future. Further study is needed to measure specific fat levels and to analyze specific active compounds in the ERP which can modulate gene expression and interact with protein targets in lipid metabolism.